Upadacitinib Monotherapy in Vitiligo Associated with Atopic Dermatitis: Killing Two Birds with One Stone - Lina Maria Magnanimi; Andrea De Berardinis; Maria Esposito; Maria Concetta Fargnoli (Case Reports in Dermatology)
Introduction: An increased risk of developing vitiligo has recently been described in patients with atopic dermatitis (AD). Vitiligo and AD can be associated because of shared pathogenetic pathways, including alterations in the Janus kinases/signal transducer and activator of transcription (JAK/STAT) signaling, suggesting JAK inhibitors as a promising new therapeutic approach in vitiligo. Case Presentation: We describe a 25-year-old woman diagnosed with AD since childhood and subsequent onset of slowly progressive vitiligo at the age of 16. Systemic therapy with JAK1 inhibitor upadacitinib 15 mg daily was started, after a medical and laboratory evaluation to exclude pregnancy and other contraindications. Progressive improvement of AD was observed after the first weeks of treatment with clinical remission at week 16. At the same time, clear improvement of vitiligo was observed with an almost complete remission achieved at week 28 of treatment. Conclusion: The remission of both AD and vitiligo achieved with upadacitinib monotherapy supports the therapeutic utility of inhibition of JAK 1 signaling in these patients.